Toward a Conceptual Framework for Resilient EdTech Integration: A Systematic Literature Review on Spiritual Leadership and Risk Management in Islamic Boarding Schools - Ali Muhlisin; Muhamad Towil Akhirudin; Fajar Suryono; Nurdiyanto Khusniahadi (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2025)
This article presents a systematic literature review to construct a conceptual framework for resilient Educational Technology (EdTech) integration in Islamic boarding schools (pesantren). The objective is to synthesise insights from spiritual leadership and risk management to formulate a model for organisational resilience in the digital era. The study employs the Systematic Literature Review (SLR) method with a PRISMA protocol, analysing articles published in Scopus between 2019 and 2024. The core findings and discussion identify two key pillars: spiritual leadership drives vision and adaptive culture, while risk management serves as the operational shield. These elements synergise through mediating EdTech, which enables external buffering and internal capacity strengthening. EdTech allows pesantren to shift from reactive practices to proactive strategies, enhancing resilience against disruptions. The review concludes that a resilient EdTech integration framework requires a balance between spiritual values, risk governance, and strategic technology adoption. The practical implication is a guide for pesantren administrators to design digital transformation aligned with their foundational ethos. Future Research should empirically test this framework and explore context-specific implementation models for pesantren.